FeSiAl-Fe composite target material and preparation method thereof

Through the preparation method of FeSiAl-Fe composite target, the density and uniformity of the target are improved by using the molding and SPS sintering processes, and the addition of ceramic rings by machining and adding ceramic rings, the problems of the existing FeSiAl alloy targets are solved, and the arc running problems in the coating process are achieved, achieving efficient and stable coating performance.

CN119549719APending Publication Date: 2025-03-04苏州六九科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411684555.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing FeSiAl alloy targets have low density, uneven composition, poor mechanical processing performance, and arc-running problems are prone to occur during PVD arc ion coating.

Method used

The preparation method of FeSiAl-Fe composite target material is adopted to obtain a dense pure Fe cold pressed blank by molding, and combined with the SPS discharge plasma sintering process, sintering and densifying under vacuum conditions, and ceramic rings are added during the machining process to improve the stability of the target material.

Benefits of technology

The high density, composition uniformity and good mechanical processing performance of FeSiAl-Fe composite targets are achieved, and the arc run-off phenomenon during PVD coating is avoided, and the coating performance and production efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005149113010000011
    Figure HDA0005149113010000011
Patent Text Reader

Abstract

The invention relates to the technical field of powder metallurgy materials, and particularly discloses a FeSiAl-Fe composite target material and a preparation method thereof. The preparation method of the FeSiAl-Fe composite target material specifically comprises the following steps that pure Fe powder is subjected to compression molding, and a bottom layer pure Fe cold-pressed blank with the density being 60%-85% is obtained; the bottom-layer cold-pressed blank is loaded into the bottom layer of a graphite mold, and FeSiAl alloy powder is evenly filled above the bottom-layer cold-pressed blank; the graphite mold is placed in an SPS discharge plasma sintering furnace, sintering densification is carried out under the vacuum condition, and after cooling, demolding is carried out to obtain a FeSiAl-Fe composite pressed blank; and the composite pressed blank is machined, and the FeSiAl-Fe composite target material is obtained. According to the technical scheme, the FeSiAl-Fe composite target material which is high in density, low in impurity element content, uniform in structure and excellent in coating performance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of powder metallurgy materials, and in particular to a FeSiAl-Fe composite target material and a preparation method thereof. Background Art

[0002] FeSiAl thin film material has good soft magnetic properties, such as high saturation flux density, low coercivity and wear resistance, and is suitable for making high-density magnetic head materials and thin film inductor materials. In recent years, it has been successfully used as a magnetic pole material for thin film magnetic heads, attracting widespread attention.

[0003] With the continuous development of coating applications, as the core raw material for preparing FeSiAl thin films by PVD physical vapor deposition technology, the market demand for FeSiAl alloy targets is increasing. It is known that FeSiAl alloy has a magnetocrystalline anisotropy constant K1 and magnetostriction coefficient close to zero near the composition of 9.6wt% Si, 5.4wt% Al, and the remainder Fe, thus showing excellent soft magnetic properties. The alloy of this composition is usually called Sendust alloy, which is a well-known soft magnetic material. At present, the technical barriers to the preparation of FeSiAl alloy targets with this composition are very high. On the one hand, the melting points of the three components are very different, and it is difficult to fully densify by sintering, which is easy to produce component segregation; on the other hand, because FeSiAl alloy is hard and brittle, it is easy to crack and difficult to machine. In addition, in the process of PVD arc ion plating thin film deposition, it is necessary to control the magnetic field distribution on the surface of the cathode target to affect the distribution of positive ions in the space in front of the cathode, thereby indirectly changing the ablation of the cathode target. When the soft magnetic FeSiAl alloy is used as the target material, most of the magnetic flux generated by the external magnetic field will flow through the closed-loop short-circuit of the magnetic circuit inside the target material, interfering with the magnetic field distribution on the surface of the cathode FeSiAl alloy target material and even producing magnetic shielding, which makes it impossible to stably etch the FeSiAl alloy target material, resulting in arc running and arc breaking.

[0004] Therefore, it is of great significance to study and develop a preparation method of FeSiAl composite target material to solve the problems of low density, uneven composition, poor machining performance and arc running during arc ion plating. Summary of the invention

[0005] In order to improve the density of FeSiAl alloy target material, the present application provides a FeSiAl-Fe composite target material and a preparation method thereof.

[0006] The present application provides a FeSiAl-Fe composite target material, which adopts the following technical solution:

[0007] A method for preparing a FeSiAl-Fe composite target material, characterized in that it specifically comprises the following steps:

[0008] (1) forming the pure Fe powder by molding to obtain a bottom layer of pure Fe cold pressed blank with a density of 60% to 85%;

[0009] (2) placing the bottom cold pressed billet into the bottom layer of the graphite mold, and evenly filling the top with FeSiAl alloy powder;

[0010] (3) placing the graphite mold in an SPS spark plasma sintering furnace, sintering and densifying under vacuum conditions, and after cooling, demolding to obtain a FeSiAl-Fe composite compact;

[0011] (4) The composite compact is machined to obtain a FeSiAl-Fe composite target.

[0012] Preferably, the FeSiAl-Fe composite target material is a double-layer structure, with FeSiAl alloy as the upper layer of the target material and pure Fe material as the bottom layer of the target material; the FeSiAl alloy is composed of the following components by weight percentage: Si = 8-10wt%, Al = 5-7wt%, and Fe as the balance; the FeSiAl-Fe composite target material is surrounded by a ceramic ring.

[0013] Preferably, the specification parameters of each raw material are as follows: Fe powder uses a purity of ≥99.5wt%, -100 mesh Fe powder; FeSiAl alloy powder uses a purity of ≥99.5wt%, -300 mesh FeSiAl alloy powder.

[0014] Preferably, in step (1), the density of the bottom pure Fe cold pressed blank is 65% to 80%, and the thickness of the pressed blank is 8-40 mm; the process parameters of the compression molding are: pressure 150-850 tons, holding time 0-10 s; the compression mold is mold steel.

[0015] Furthermore, the process parameters of the compression molding are: pressure 200-800 tons, and holding time 0-3s.

[0016] The present application configures a pure Fe bottom layer material with good comprehensive mechanical properties on the bottom layer of the FeSiAl-Fe alloy, which solves the problem that threads, steps, etc. cannot be processed due to the intrinsic brittleness of the material; the semi-dense Fe pressed billet is prepared by the above technical solution, which can ensure the straightness of the boundary line of the composite target. Fe blocks with too high density will produce stress cracks due to the large difference in thermal expansion coefficients between the target layer FeSiAl and the bottom layer pure Fe. Therefore, the density of the bottom layer pure Fe cold pressed billet of the present application is controlled to be 60% to 85%; further, the density of the bottom layer pure Fe cold pressed billet is controlled to be 65% to 80%.

[0017] Preferably, in step (3), the process parameters of the SPS spark plasma sintering treatment are: temperature 800-1100°C, pressure 20-40MPa, vacuum degree 10 -1Pa-10 -3 Pa, heat preservation and pressure holding time 1-30min.

[0018] Furthermore, in step (3), the process parameters of the SPS spark plasma sintering treatment are: heating to 500-700°C at a heating rate of 20-90°C / min, keeping warm for 5-15min; then heating to 800-1100°C at a heating rate of 20-40°C / min, keeping warm for 1-20min, pressure 20-40MPa, vacuum degree 10 -1 Pa-10 -3 Pa.

[0019] Furthermore, in step (3), the process parameters of the SPS spark plasma sintering treatment are: heating to 550-650°C at a heating rate of 20-70°C / min, keeping warm for 5-15min; then heating to 850-1000°C at a heating rate of 20-30°C / min, keeping warm for 5-10min, pressure 25-40MPa, vacuum degree 10 -1 Pa-10 -3 Pa.

[0020] The technical solution provided in the present application is a method for preparing a FeSiAl-Fe composite target material. In the SPS spark plasma sintering treatment, the heating rate is first fast and then slow to prevent overburning or liquid phase at the final sintering temperature, while shortening the sintering cycle; the greater the sintering pressure, the higher the density of the pressed green sheet; the two insulation steps are set to reduce the content of impurity elements N and O in the target material, so as to obtain a high-density FeSiAl-Fe composite target material, so that the target layer FeSiAl forms a metallurgical bond with the underlying pure Fe.

[0021] Preferably, in step (3), the cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 550-650°C at a cooling rate of 5-15°C / min, and then cooling to room temperature in the furnace.

[0022] In the method for preparing a FeSiAl-Fe composite target material, the technical solution provided in the present application adopts temperature-controlled cooling. On the one hand, the reason is that FeSiAl has high intrinsic brittleness, and temperature-controlled cooling can prevent stress cracks from being generated inside the FeSiAl target layer; on the other hand, the reason is that there is still a certain difference in thermal expansion coefficient between the target layer FeSiAl and the underlying pure Fe, and slow cooling can effectively prevent cracks from being generated in the FeSiAl-Fe bonding area.

[0023] Preferably, in step (4), the specific steps of machining are: A rough machining: removing the carburized layer on the end face and outer circle of the composite compact; B boundary alignment: aligning the interface between the FeSiAl target layer and the Fe bottom layer so that the interface deviation is controlled within ±1 mm; C fine machining: machining the finished FeSiAl-Fe composite target according to the drawing, turning the steps, machining the external threads, drilling the threaded holes, and finally grinding the end face to obtain the finished FeSiAl-Fe composite target; D combined ceramic ring: combining the ceramic ring on the periphery of the FeSiAl-Fe composite target.

[0024] In the specific steps of machining, the blank is first processed by wire cutting to a nearly finished size, and then the outer circle, steps, and threads are turned, and finally the large surface is ground instead of turning; this step can effectively prevent chipping of edges and corners.

[0025] In the second aspect, the present application provides a FeSiAl-Fe composite target material, which is prepared by any of the preparation methods described above, wherein the FeSiAl-Fe composite target material is a double-layer structure, with FeSiAl alloy as the upper layer of the target material and pure Fe material as the bottom layer of the target material; the FeSiAl alloy is composed of the following components by weight percentage: Si = 8-10wt%, Al = 5-7wt%, and Fe as the balance; the FeSiAl-Fe composite target material is surrounded by a ceramic ring; the density of the FeSiAl-Fe composite target material is ≥6.8g / cm 3 , impurity element N≤300ppm, impurity element O≤1300ppm.

[0026] In summary, the technical solution of this application has the following effects:

[0027] The FeSiAl-Fe dual composite structure target prepared by the method of the present application has high density, uniform structure, and is easy to process and shape. The target can be used stably without arcing during PVD arc ion plating, has excellent coating performance, and has the advantages of short production cycle and high production efficiency.

[0028] Compared with the conventional FeSiAl alloy preparation method, the present invention adopts a powder metallurgy method, using FeSiAl alloy powder and pure Fe powder instead of elemental powder, and a matching SPS spark plasma sintering process to achieve rapid densification of FeSiAl-Fe alloy target. The obtained FeSiAl-Fe alloy target has a high density (density ≥6.8g / cm 3 ), the content of impurity elements N and O is low (N≤300ppm, O≤1300ppm), the composition is uniform without segregation, and the sintering efficiency is high.

[0029] At the same time, through the design of the double composite target structure, on the one hand, a pure Fe bottom material with good comprehensive mechanical properties is configured on the bottom layer of the FeSiAl-Fe alloy, which solves the problem of threads, steps and other processing problems caused by the intrinsic brittleness of the material; on the other hand, a ceramic ring is combined on the outer side of the FeSiAl-Fe composite target through threaded connection to solve the problem of normal coating of the magnetic target due to the interference and shielding effect of its own magnetism on the external magnetic field during arc ion plating. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a microstructure diagram of the FeSiAl-Fe composite target prepared in Example 1 of the present application (scanning electron microscope image - 3000 times).

[0031] Figure 2 This is a picture of the finished product of the FeSiAl-Fe composite target prepared in Example 1 of the present application.

[0032] Figure 3 This is a picture of the finished product of the FeSiAl-Ti composite target prepared in Comparative Example 1 of the present application.

[0033] Figure 4 This is the microstructure diagram of the FeSiAl-Fe composite target prepared in Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0034] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0035] Example

[0036] Example 1

[0037] Example 1 provides a FeSiAl-Fe composite target.

[0038] The method for preparing the FeSiAl-Fe composite target in Example 1 specifically comprises the following steps:

[0039] (1) Pure Fe powder is subjected to compression molding to obtain a bottom layer pure Fe cold pressed blank with a density of 70% and a size of D110×17.5 mm; the Fe powder is of a purity of ≥99.5wt% and -100 mesh; the process parameters of the compression molding are a pressure of 500 tons and a holding time of 2 seconds;

[0040] (2) loading the bottom cold pressed billet into the bottom layer of the graphite mold, and evenly filling the top with FeSiAl alloy powder; the FeSiAl alloy powder is composed of the following components by weight percentage: Si = 9wt%, Al = 6wt%, and Fe as the balance; the FeSiAl alloy powder is a -300 mesh FeSiAl alloy powder with a purity of ≥99.5wt%;

[0041] (3) The graphite mold was placed in an SPS spark plasma sintering furnace and sintered and densified under vacuum conditions. After cooling, the mold was demolded to obtain a FeSiAl-Fe composite compact. The process parameters of the SPS spark plasma sintering treatment were: heating to 600°C at a heating rate of 50°C / min and holding for 10 min; then heating to 960°C at a heating rate of 25°C / min and holding for 8 min, with a pressure of 30 MPa and a vacuum degree of 10 -2 Pa; cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 600°C at a cooling rate of 10°C / min, and then cooling to room temperature with the furnace;

[0042] (4) The FeSiAl-Fe composite compact obtained in step (3) is machined to obtain a FeSiAl-Fe composite target product; the specific steps of machining are as follows: A rough machining: wire cutting is used to obtain a machined blank with a size of D102×24 mm, and the carburized layer is removed; B interface alignment: general turning is used to align the FeSiAl-Fe interface, and the size of the Fe bottom layer is D102×(11±1) mm; C fine machining: steps, external threads M90, and M2 threaded holes are machined in the Fe bottom layer in sequence, and finally the end face is polished to obtain a FeSiAl-Fe composite target product with a size of D100×20 mm; D combined ceramic rings are used to obtain a FeSiAl-Fe dual composite target with a size of D100×40 mm.

[0043] A total of 10 finished products were processed using the method of this embodiment. During the SPS sintering and machining process, there were no defects such as chipping, corner dropping, and cracks, and the qualified rate of finished products was 100%.

[0044] Example 2-11

[0045] Examples 2-11 each provide a FeSiAl-Fe composite target.

[0046] The difference between the above embodiment and embodiment 1 is that the specific process parameters of the SPS spark plasma sintering treatment are different, as shown in Table 1.

[0047] Table 1 Specific process parameters of SPS spark plasma sintering in Examples 1-11

[0048]

[0049] The process parameters of the above embodiment are the same as those of embodiment 1.

[0050] Examples 12-13

[0051] Examples 12-13 each provide a FeSiAl-Fe composite target.

[0052] The difference between the above embodiment and embodiment 1 is that the cooling method is different.

[0053] In Example 12: temperature-controlled cooling is adopted, and the specific steps are: cooling to 650°C at a cooling rate of 5°C / min, and then cooling to room temperature in the furnace.

[0054] In Example 13: temperature-controlled cooling is adopted, and the specific steps are: cooling to 550°C at a cooling rate of 15°C / min, and then cooling to room temperature in the furnace.

[0055] The process parameters of the above embodiment are the same as those of embodiment 1.

[0056] Comparative Example

[0057] Comparative Example 1

[0058] This comparative example provides a FeSiAl-Ti composite target.

[0059] The preparation method of the FeSiAl-Ti composite target in this comparative example specifically includes the following steps:

[0060] (1) Pure Ti powder is molded to obtain a bottom pure Ti cold pressed billet with a density of 70% and a size of D110*17.5 mm; the Ti powder is -300 mesh Ti powder with a purity of ≥99.7wt%; the molding process parameters are a pressure of 550 tons and a holding time of 3s;

[0061] (2) The bottom layer of pure Ti cold pressed billet is loaded into the bottom layer of graphite mold, and FeSiAl alloy powder is loaded on the top and laid flat; the FeSiAl alloy powder is composed of the following components by weight percentage: Si = 9wt%, Al = 6wt%, and Fe is the balance; the FeSiAl alloy powder adopts a purity of ≥99.5wt%, -300 mesh FeSiAl alloy powder;

[0062] (3) The graphite mold was placed in an SPS spark plasma sintering furnace and sintered and densified under vacuum conditions. After cooling, the mold was demolded to obtain a FeSiAl-Ti composite compact. The process parameters of the SPS spark plasma sintering treatment were as follows: heating to 600°C at a heating rate of 50°C / min and holding for 10 min; then heating to 960°C at a heating rate of 25°C / min and holding for 8 min, with a pressure of 30 MPa and a vacuum degree of 10 -2 Pa; cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 600°C at a cooling rate of 10°C / min, and then cooling to room temperature with the furnace;

[0063] (4) The FeSiAl-Ti composite compact obtained in step (3) is machined to obtain a finished FeSiAl-Ti composite target; the specific steps of machining are as follows: A rough machining: wire cutting is used to obtain a machined blank with a size of D102×24 mm, and the carburized layer is removed; B interface alignment: general turning is used to align the FeSiAl-Ti interface, and the size of the Ti bottom layer is D102×(11±1) mm; C fine machining: steps, external threads M90, and M2 threaded holes are machined in the Ti bottom layer in sequence, and finally the end face is polished to obtain a finished FeSiAl-Ti composite target with a size of D100×20 mm; D combined ceramic rings are used to obtain a FeSiAl-Ti dual composite target with a size of D100×40 mm.

[0064] Using this comparative method, a total of 4 FeSiAl-Ti composite targets were prepared. During the processing of the finished products, it was found that a large number of stress cracks were generated in the outer circle direction of the FeSiAl target, such as Figure 3 As shown, the qualified rate of finished product processing is 0.

[0065] Comparative Example 2

[0066] This comparative example provides a FeSiAl single-layer target material.

[0067] The preparation method of the FeSiAl single-layer target in this comparative example specifically includes the following steps:

[0068] (1) FeSiAl alloy powder is loaded into the bottom of a graphite mold; the FeSiAl alloy powder is composed of the following components by weight percentage: Si = 9wt%, Al = 6wt%, and Fe is the balance; the FeSiAl alloy powder adopts a purity of ≥99.5wt%, -300 mesh FeSiAl alloy powder;

[0069] (2) The graphite mold was placed in an SPS spark plasma sintering furnace and sintered and densified under vacuum conditions. After cooling, the mold was demolded to obtain a FeSiAl compact. The process parameters of the SPS spark plasma sintering treatment were as follows: heating to 600°C at a heating rate of 50°C / min and holding for 10 min; then heating to 960°C at a heating rate of 25°C / min and holding for 8 min, with a pressure of 30 MPa and a vacuum degree of 10 -2 Pa; cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 600°C at a cooling rate of 10°C / min, and then cooling to room temperature with the furnace;

[0070] (3) The single-layer target material compact obtained in step (2) is machined to obtain a single-layer FeSiAl target material product; the specific steps of machining are: A rough machining: wire cutting to obtain a machined blank with a size of D101.5×22 mm, and removing the carburized layer; B fine machining: sequentially machining a step, an external thread M90, an M2 threaded hole on the target material, and finally polishing the end face to obtain a single-layer FeSiAl product with a size of D100×20 mm; D combined ceramic ring to obtain a FeSiAl composite target with a size of D100×40 mm.

[0071] By adopting the comparative example method, a total of 3 FeSiAl single-layer targets were prepared, and the obtained compacts were intact and met the technical requirements. However, the single-layer FeSiAl target was brittle, and the edge collapsed seriously during the step processing. The internal and external threads could not be processed, and finally no finished product was obtained; the corresponding finished product qualification rate was 0.

[0072] Comparative Example 3

[0073] Comparative Example 3 provides a FeSiAl-Fe composite target.

[0074] The preparation method of the FeSiAl-Fe composite target in Comparative Example 3 uses element powder mixing instead of FeSiAl alloy powder, and specifically includes the following steps:

[0075] (1) Pure Fe powder is subjected to compression molding to obtain a bottom layer pure Fe cold pressed blank with a density of 70% and a size of D110×17.5 mm; the Fe powder adopts a purity of ≥99.5wt% and -100 mesh Fe powder; the process parameters of the compression molding are a pressure of 500 tons and a holding time of 3 seconds;

[0076] (2) According to the weight percentage composition of Fe=85wt%, Si=9wt%, Al=6wt%, Fe powder, Si powder, and Al powder are mixed evenly in a three-dimensional mixer to obtain FeSiAl mixed powder. The Fe powder is 99.5wt% pure iron powder, -300 mesh; the Si powder is 99.96wt% pure silicon powder, -300 mesh; the Al powder is 99.8wt% pure aluminum powder, -300 mesh;

[0077] (3) placing the bottom pure Fe cold pressed billet into the bottom layer of the graphite mold, and evenly filling the FeSiAl mixed powder obtained in step (2) on top of the billet;

[0078] (4) The graphite mold was placed in an SPS spark plasma sintering furnace and sintered and densified under vacuum conditions. After cooling, the mold was demolded to obtain a FeSiAl-Fe composite compact. The process parameters of the SPS spark plasma sintering treatment were: heating to 600°C at a heating rate of 50°C / min and holding for 10 min; then heating to 960°C at a heating rate of 25°C / min and holding for 8 min, with a pressure of 30 MPa and a vacuum degree of 10 -2 Pa; cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 600°C at a cooling rate of 10°C / min, and then cooling to room temperature with the furnace;

[0079] (5) The composite compact obtained in step (4) is machined to obtain a FeSiAl-Fe composite target. The specific machining steps are exactly the same as those in Example 1.

[0080] Although the composite target material obtained in this comparative example has no edge collapse or cracking, the FeSiAl target layer has an uneven structure, microscopic component segregation, and Fe-rich and Fe-poor regions. Figure 4 shown.

[0081] Comparative Example 4

[0082] Comparative Example 4 provides a FeSiAl-Fe composite target.

[0083] The difference between Comparative Example 4 and Example 1 is that the FeSiAl-Fe composite target material is prepared by vacuum hot pressing sintering process instead of SPS sintering process. Except for the specific sintering process parameters, the other process steps are exactly the same.

[0084] The vacuum hot pressing sintering process parameters are: first, heating up to 600℃ at a heating rate of 20℃ / min and keeping it for 60min; then heating up to 1050℃ at a heating rate of 8℃ / min and keeping it for 90min, with a pressure of 30MPa and a vacuum degree of 10. -2 Pa; cooling adopts temperature-controlled cooling, and the specific steps are: cooling to 600°C at a cooling rate of 10°C / min, and then cooling to room temperature with the furnace.

[0085] Although the sintering densification was carried out under conditions of higher temperature and longer holding time in this comparative example, the obtained FeSiAl target material had a low density and many voids remained in the microstructure.

[0086] Comparative Example 5

[0087] Comparative Example 5 provides a FeSiAl-Fe composite target.

[0088] The difference between Comparative Example 5 and Example 1 is that the machining steps of step (3) are different, specifically: no rough machining, direct fine machining; A fine machining step: sequentially machining a step, an external thread M90, an M2 threaded hole on the Fe bottom layer, and finally polishing the end face to obtain a FeSiAl-Fe composite target product with a size of D100×20mm; B combined ceramic rings to obtain a FeSiAl-Fe dual composite target with a size of D100×40mm.

[0089] A total of 10 finished products were processed using the machining method of this comparative example, and the qualified rate of the finished products was 30%.

[0090] Comparative Example 6

[0091] Comparative Example 6 provides a FeSiAl-Fe composite target.

[0092] The difference between comparative example 6 and example 1 is that the machining steps of step (3) are different, specifically: the end face grinding step in the finishing process is changed to end face turning. A rough machining: wire cutting to obtain a D102×24mm machining blank, remove the carburized layer; B interface alignment: general turning to align the FeSiAl-Fe interface, the Fe bottom layer size is D102×(11±1)mm; C finishing: sequentially process the Fe bottom layer to produce a step, an external thread M90, an M2 threaded hole, and turn the end face to obtain a FeSiAl-Fe composite target product with a size of D100×20mm; D combined ceramic ring to obtain a FeSiAl-Fe dual composite target with a size of D100×40mm.

[0093] Using the method of this comparative example, a total of 10 finished products were processed, and the qualified rate of finished products was 25%.

[0094] Performance testing

[0095] (1) Microstructure and morphology

[0096] Figure 1 The microstructure diagram of the FeSiAl-Fe composite target prepared in Example 1 of the present application shows that the target has a uniform structure without component segregation, and the average grain size is about 13 μm.

[0097] Figure 2 This is a picture of the finished product of the FeSiAl dual composite target prepared in Example 1 of the present application. The finished product has a good appearance without chipping or cracks.

[0098] (2) Density: Density is measured by the Archimedean displacement method.

[0099] (3) Impurity element content: N / O content was measured by inert gas fusion infrared thermal conductivity method.

[0100] Test results: as shown in Table 3.

[0101] Table 3 Performance test results of FeSiAl-Fe composite targets in Examples 1-13 and Comparative Examples

[0102]

[0103] Combined with Table 3, by comparing the test results of the embodiment and the comparative example, the method provided in the present application prepares a FeSiAl-Fe dual-composite structure target material, which has the advantages of high density, low content of impurity elements N and O (N≤300ppm, O≤1300ppm), uniform composition without segregation, easy processing and molding, and high sintering efficiency.

[0104] In Comparative Example 1, a FeSiAl-Ti composite target prepared by using a pure Ti cold pressed billet as the bottom layer has a large number of stress cracks in the outer circumferential direction of the FeSiAl target, such as Figure 3 shown.

[0105] In Comparative Example 2, a FeSiAl single-layer target was prepared, and the FeSiAl compact obtained after SPS sintering was normal. However, the single-layer FeSiAl target was very brittle, and the edge collapsed seriously during the processing, and the external thread could not be processed.

[0106] Comparative Example 3 uses element mixed powder instead of FeSiAl alloy powder. Although the obtained FeSiAl-Fe composite target has no edge collapse and cracking, the FeSiAl target has an uneven structure and microscopic component segregation, specifically, there are Fe-rich areas and Fe-poor areas in the microstructure, such as Figure 4 shown.

[0107] Although Comparative Example 4 adopts a vacuum hot pressing sintering process with a higher temperature and a longer holding time to prepare the FeSiAl-Fe composite target instead of the SPS sintering process, the density of the obtained FeSiAl target is low and there are many residual pores in the target.

[0108] By comparing the test results of Examples 1-11, in the process of preparing the target material, the process parameters of the SPS spark plasma sintering treatment are controlled as follows: heating to 500-700°C at a heating rate of 20-90°C / min and keeping warm for 5-15min; then heating to 800-1100°C at a heating rate of 20-40°C / min and keeping warm for 1-20min, with a pressure of 20-40MPa and a vacuum degree of 10 - 1 Pa-10 -3 Pa can improve the comprehensive performance of the target material.

[0109] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a FeSiAl-Fe composite target, characterized in that: The specific steps include: (1) Pure Fe powder is molded to obtain a bottom layer of pure Fe cold pressed blank with a density of 60%-85%; (2) Loading the bottom cold pressed billet into the bottom layer of the graphite mold, and evenly filling the FeSiAl alloy powder on top of it; (3) placing the graphite mold in an SPS spark plasma sintering furnace, sintering and densifying under vacuum conditions, and demolding to obtain a FeSiAl-Fe composite compact after temperature-controlled cooling; (4) The composite compact is machined to obtain a FeSiAl-Fe composite target.

2. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: The FeSiAl-Fe composite target material has a double-layer structure, with FeSiAl alloy as the upper layer of the target material and pure Fe material as the bottom layer of the target material; the FeSiAl alloy is composed of the following components by weight percentage: Si=8-10wt%, Al=5-7wt%, and Fe as the balance; the FeSiAl-Fe composite target material is peripherally combined with a ceramic ring.

3. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: The specific specifications of the raw materials are as follows: Fe powder uses a purity of ≥99.5wt%, -100 mesh Fe powder; FeSiAl alloy powder uses a purity of ≥99.5wt%, -300 mesh FeSiAl alloy powder.

4. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: In step (1), the density of the bottom pure Fe cold pressed blank is 65%-80%, and the thickness of the pressed blank is 8-40 mm; the process parameters of the compression molding are: pressure 150-850 tons, holding time 0-10 s; the compression mold is mold steel.

5. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: In step (3), the process parameters of SPS spark plasma sintering treatment are: temperature 800-1100°C, pressure 20-40MPa, vacuum degree 10 -1 Pa-10 - 3 Pa, heat preservation and pressure holding time 1-30min.

6. The method for preparing the FeSiAl-Fe composite target according to claim 5, characterized in that: In step (3), the process parameters of the SPS spark plasma sintering treatment are: heating to 500-700°C at a heating rate of 20-90°C / min and keeping at that temperature for 5-15min; then heating to 800-1100°C at a heating rate of 20-40°C / min and keeping at that temperature for 1-20min, pressure of 20-40MPa, vacuum degree of 10 -1 Pa-10 -3 Pa.

7. The method for preparing the FeSiAl-Fe composite target according to claim 6, characterized in that: In step (3), the process parameters of the SPS spark plasma sintering treatment are: heating to 550-650°C at a heating rate of 20-70°C / min, keeping warm for 5-15min; then heating to 850-1000°C at a heating rate of 20-30°C / min, keeping warm for 5-10min, pressure 25-40MPa, vacuum degree 10 -1 Pa-10 -3 Pa.

8. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: In step (3), the cooling is carried out by temperature-controlled cooling, and the specific steps are: cooling to 550-650°C at a cooling rate of 5-15°C / min, and then cooling to room temperature in the furnace.

9. The method for preparing the FeSiAl-Fe composite target according to claim 1, characterized in that: In step (4), the specific steps of the machining are: A rough machining: removing the carburized layer on the end face and outer circle direction of the FeSiAl-Fe composite compact in step (3); B boundary alignment: aligning the interface between the FeSiAl target layer and the Fe bottom layer so that the interface deviation is controlled within ±1 mm; C fine machining: machining the finished FeSiAl-Fe composite target according to the drawing, turning the steps, machining the external threads, drilling the threaded holes, and finally grinding the end face to obtain the finished FeSiAl-Fe composite target; D combined ceramic ring: combining the ceramic ring on the periphery of the FeSiAl-Fe composite target.

10. A FeSiAl-Fe composite target, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9; the density of the FeSiAl-Fe composite target is ≥ 6.8 g / cm 3 , impurity element N≤300ppm, impurity element O≤1300ppm.